2003
DOI: 10.1080/1042517031000154952
|View full text |Cite
|
Sign up to set email alerts
|

Human Fast Skeletal Myosin Light Chain 2 cDNA: Isolation, Tissue Specific Expression of the Single Copy Gene, Comparative Sequence Analysis of Isoforms and Evolutionary Relationships

Abstract: A cDNA clone encoding human fast skeletal myosin regulatory light chain (HSRLC) has been isolated and characterized from a fetal muscle cDNA library. The cDNA contains the coding sequence of 170 amino acids (aa) and 58 and 91 nucleotides in the 5' and 3' untranslated regions (UTRs), respectively. HSRLC is encoded by a single copy gene in the human genome and shows a tissue-specific pattern of expression in skeletal muscle. Comparison of derived amino acid sequence of HSRLC with database sequences reveals highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, the functional involvement of these TFs in the regulation of fish mlc2f genes has yet not been determined. In contrast, previous studies on the mammalian mlc2f have reported that downregulation of AP-1, Sp-1, and NF-κB should be a prerequisite for the onset of myocyte differentiation (Lehtinen et al, 1996;Sachdev et al, 2003).…”
Section: Rfp Expression In Pojmlc2rfp-microinjected Embryosmentioning
confidence: 60%
“…However, the functional involvement of these TFs in the regulation of fish mlc2f genes has yet not been determined. In contrast, previous studies on the mammalian mlc2f have reported that downregulation of AP-1, Sp-1, and NF-κB should be a prerequisite for the onset of myocyte differentiation (Lehtinen et al, 1996;Sachdev et al, 2003).…”
Section: Rfp Expression In Pojmlc2rfp-microinjected Embryosmentioning
confidence: 60%
“…It is proposed that phosphorylation of the RLC increases Ca 2+ sensitivity by bringing the myosin heads into closer proximity with actin (MacIntosh, 2003), and it seems entirely plausible that glutathionylation of the RLC could have similar effects. Consistent with this, the RLC of fast‐twitch muscle has two cysteine residues to act as sites for glutathionylation, one of which (Cys‐129) is crucial to regulatory function (Sachdev et al 2003), whereas the RLC of slow‐twitch muscle has no cysteine residues at all (Dalla Libera et al 1989) and so could not be subject to glutathionylation.…”
Section: Discussionmentioning
confidence: 87%
“…Eight-hundred and eighty-nine genes (13.0%, p < 0.01) are significantly differently expressed during pre-hatching (stages 1-35) versus post-hatching (stages 36-40) (Figure 3); 417 genes (47%) have higher expression levels before hatching, while 472 genes (53%) are up regulated after hatching (Additional File 7). Several post-hatch up regulated genes have important functions in muscle tissue development and movement including parvalbumins alpha and beta (calcium-binding proteins involved in muscle relaxation have 5-9-fold higher expression post-hatch [10,11]), myosin regulatory light chain, skeletal muscle isoform (6.1-fold increase [12]), myosin light chain 3, skeletal muscle gene (5.2-fold increase [13]), myosin binding protein C (3.4-fold increase [14,15]) and troponins I, T and C (~3-fold increases [16]). Increased transcript levels of these genes suggest increases in movement and muscle activity of a free-swimming Fundulus compared to restricted movement within a chorion microenvironment before hatching.…”
Section: Resultsmentioning
confidence: 99%